Strategi Marketing Mix Dalam Menghadapi Pandemi Covid-19 (Studi Kasus Pada Jolly Coffee Surabaya) - Siti Nur Wahyu Ningsih; Aida Octavia Milasari; Muchammad Saifuddin (Jurnal Manajemen dan Inovasi (MANOVA), 2021)
The cafe business in Indonesia is increasingly increased its growth. This is a business field for business activists. Surely a cafe has its own marketing system or what we can call a Marketing Mix. The purpose of this study is to identify the implementation of marketing strategies in cafes in Indonesia, especially in Surabaya. This research uses qualitative methods, namely through observation, document study and interviews with several relevant informants. The results of this study indicate that Cafe Jolly Coffee Surabaya uses a marketing strategy which I believe is appropriate to attract consumer interest and is also used to compete in the cafe sector.